Cu3Si-doped porous-silicon particles prepared by simplified chemical vapor deposition method as anode material for high-rate and long cycle lithium-ion batteries - Woo, Jae-Young; Kim, A. -Young; Kim, Min Kyu; Lee, Sang-Hyup; Sun, Yang-Kook; Liu, Guicheng; Lee, Joong Kee (ELSEVIER SCIENCE SA, 2017)
To provide a possible proposal for the large-scale production of a high performance silicon-based anode material in the lithium battery industry, a Cu3Si nanoparticle doped porous-silicon particles was prepared via a simplified chemical vapor deposition (CVD) process and heat treatment for the first time. In this work, the Cu3Si doping content was optimized by discharge/charge, transmission electron microscopy and electrochemical impedance spectroscopy tests. The results show that compared with the porous-silicon (PS) particles, the Cu3Si doping significantly enhanced the discharge capacity, coulombic efficiency, capacity retention, and high-rate performance of the silicon-based anode. The optimum performance with a discharge capacity of 3036.4 mA h g(-1) and a coulombic efficiency of 90.49% at the first cycle (after the first three formation cycles) and a capacity retention of 58.72% after 100 cycles occurred at a Cu3Si doping content of 2 wt%. The reasons for this are as follows: the PS particles with a similarly silicon nanorod structure accommodated the volume change to maintain the mechanical stability of the electrode during the cycling process; during the simplified CVD process, the nanostructure of silicon was retained; the high conductivity due to Cu3Si doping decreased the formation resistance of the solid-electrolyte interphase (SEI) film and enhanced the diffusion coefficient of Li+ inside the silicon based material; both fewer Cu3Si doping and aggregation particles resulting from excessive Cu3Si doping yielded insufficient electrical conductivity and decreased the formation resistance of the SEI film for the silicon-based material. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: X-RAY-DIFFRACTION; RADICAL OXIDATION; THIN-FILMS; PERFORMANCE; LI; COMPOSITE; CAPACITY; CATHODE; MICRO; STABILITY